Halal Certification Policies in OIC and Non-OIC Countries: A Comparative Analysis of Indonesia, Malaysia, Thailand, And Singapore - Nailun Najla; Nur Fatwa (International Journal of Islamic Business and Management Review, 2025)
Purpose – This paper seeks to explore and compare the policies and regulatory frameworks of halal certification in both OIC member and non-member countries—specifically Indonesia, Malaysia, Thailand, and Singapore. It aims to identify the strengths, weaknesses, opportunities, and threats (SWOT) related to the implementation of halal certification systems and their implications for positioning within the global halal market. Methodology/approach – A qualitative approach was adopted using secondary data sourced from scientific literature. The analysis focused on institutional structures, certification procedures, and policy frameworks, comparing how each country governs and implements halal certification. Findings – The study reveals significant differences in the institutional and regulatory approaches to halal certification. Indonesia operates through BPJPH under the Ministry of Religious Affairs, Malaysia through JAKIM, Thailand through CICOT, and Singapore through MUIS. Each system presents distinct advantages and challenges, influencing the countries’ ability to compete as global halal hubs. Novelty/value – This study contributes a comparative perspective on halal certification between OIC and non-OIC member countries and applies a SWOT analysis framework to highlight strategic opportunities and challenges. It offers insights useful for policymakers and stakeholders aiming to enhance halal governance and competitiveness in the global halal industry.